Resolution of Inter-District/City Boundary Disputes in Indonesia (Study on Constitutional Court Decision Number 71-PS/PUU-XXI/2023) - Diyah Eka Pratiwi; Suartini Suartini; Zuhad Aji Firmantoro (Eduvest - Journal of Universal Studies, 2024)
This research discusses the regulation and process of resolving discrepancies in using Protected Rice Fields (PRF) by Indonesian laws and regulations. PRF has an important role in protecting strategic food resources and maintaining national food security. This research aims to analyze the regulatory framework governing PRF and identify challenges in the resolution process, as well as present steps that can be taken to improve PRF management. This research uses a normative research approach with an analysis of applicable regulations and procedures related to PRF in Indonesia. The research results highlight the need for increased coordination between central and regional governments in determining and monitoring PRF, strict law enforcement, regular updating of PRF data, outreach to the community, providing incentives to farmers, and increasing investment in agricultural infrastructure. These steps are expected to increase the effectiveness of PRF management, which will ultimately support national food security and farmer welfare.